RESEARCH ON CONSUMER ATTITUDES OF ORGANIC FOOD CONSUMPTION IN SЕRBIA - Vlahović, Branislav; Radojević, Vuk; Živanović, Ivana (Economics of Agriculture, 2011)
In this paper authors research consumer attitudes about the purchase and consumption of organic food in the Republic of Serbia. The aim of this research is to identify main factors that influence on demand for organic agricultural products.Three quarters of respondents are not familiar with the law on organic food.Requires a significant consumer education in this direction in order to better inform and increase demand. The largest proportion of respondents (40%) have confidence in domestic organic products, which is a good basis to increase supply in the market. The largest number of interviewed persons buy organic agricultural products at the markets (40%), it is observed declining importance of the specialized shops, so-called "organic" food shops. Half of respondents believe that organic agricultural products have a high price, which is a significant limiting factor of increasing demand and consumption. Almost half of respondents are willing to pay more to purchase organic products. Three quarters of respondents consider that organic products are "healthy" nutrition, which also should represent an additional motivation for the growth of their consumption. The results indicate that consumer awareness of organic food is not yet developed and built. Also, the market for organic food is still not sufficiently developed. It is necessary to extend the range of products from organic agriculture and food industry, to have a continuous supply and to develop appropriate marketing. With good information and education of consumers consumption can be upgraded to a higher level.